1995
DOI: 10.1136/vr.136.17.439
|View full text |Cite
|
Sign up to set email alerts
|

Post mortem investigations on cetaceans found stranded on the coasts of Italy between 1990 and 1993

Abstract: Detailed pathological and virological examinations were carried out on 25 cetaceans found stranded between 1990 and 1993 on the coasts of six Italian regions (Latium, Tuscany, Apulia, Abruzzo, Veneto and Sicily). There were 16 striped dolphins (Stenella coeruleoalba), three bottlenosed dolphins (Tursiops truncatus), three Risso's dolphins (Grampus griseus), one rough-toothed dolphin (Steno bredanensis), one fin whale pup (Balaenoptera physalus), and one minke whale (Balaenoptera acutorostrata). Apart from para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 0 publications
4
58
0
Order By: Relevance
“…General descriptions of dolphin thoracic ultrasound exams have been published in marine mammal textbooks (Stone 1990, Brook et al 2001. However, there are currently no peer-reviewed publications on thoracic ultrasound techniques or findings in dolphins.A retrospective epidemiologic analysis of lung histopathology from the past 30 yr (1980 to 2010) of US Navy Marine Mammal Program data showed that the most common pulmonary pathology was pneumonia (Venn-Watson et al 2012), which is similar to findings of wild dolphin necropsies (Baker 1992, Di Guardo et al 1995, Cornaglia et al 2000, Bogomolni et al 2010. In both wild and managed dolphins, bacterial pneumonias have been reported often (Cusick & Bullock 1973, Sweeney & Ridgway 1975, Diamond et al 1979, Tangredi & Medway 1980, Howard et al 1983, Schulman et al 1997, Miller et al 1999, Dunn et al 2001, Makara et al 2007, St. Leger et al 2009), as well as fungal (Carroll et al 1968, Migaki et al 1978, Gales et al 1985, Joseph et al 1986, Schulman et al 1997, Jensen et al 1998, Reidarson et al 1998a,b, Miller et al 2002, Elad et al 2011), viral (Domingo et al.…”
mentioning
confidence: 68%
“…General descriptions of dolphin thoracic ultrasound exams have been published in marine mammal textbooks (Stone 1990, Brook et al 2001. However, there are currently no peer-reviewed publications on thoracic ultrasound techniques or findings in dolphins.A retrospective epidemiologic analysis of lung histopathology from the past 30 yr (1980 to 2010) of US Navy Marine Mammal Program data showed that the most common pulmonary pathology was pneumonia (Venn-Watson et al 2012), which is similar to findings of wild dolphin necropsies (Baker 1992, Di Guardo et al 1995, Cornaglia et al 2000, Bogomolni et al 2010. In both wild and managed dolphins, bacterial pneumonias have been reported often (Cusick & Bullock 1973, Sweeney & Ridgway 1975, Diamond et al 1979, Tangredi & Medway 1980, Howard et al 1983, Schulman et al 1997, Miller et al 1999, Dunn et al 2001, Makara et al 2007, St. Leger et al 2009), as well as fungal (Carroll et al 1968, Migaki et al 1978, Gales et al 1985, Joseph et al 1986, Schulman et al 1997, Jensen et al 1998, Reidarson et al 1998a,b, Miller et al 2002, Elad et al 2011), viral (Domingo et al.…”
mentioning
confidence: 68%
“…As in the earlier event, 4,5,21 unusually high striped dolphin mortality was recorded along the coast of Italy during this recent morbillivirus epidemic, including the Ligurian coast of northwestern Italy from August to December 2007 (F. Garibaldi and W. Mignone, personal communication). The aim of this study was to investigate possible causes of death of these animals, with emphasis on four cases of T gondii infection.…”
mentioning
confidence: 93%
“…Transplacental fetal infection was reported in a free-ranging Risso's dolphin Grampus griseus and a captive Tursiops aduncus (reviewed in Dubey et al 2003). Toxoplasmosis was often, though not always, associated with immunosuppression following a morbillivirus infection and/or high concentrations of environmental contaminants including PCBs (Di Guardo et al 1995, Mikaelian et al 2000.…”
Section: Toxoplasmosismentioning
confidence: 99%